PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL KOTA DENPASAR - Ni Putu Ayu Mirta Mahayani; I Nengah Sudja; Yenny Verawati (VALUES, 2022)
Customer loyalty has an important role in a company. The rapid pace of science and technology has demanded every government organization to display high employee performance in order to achieve goals and win the competition so that performance driving factors are needed such as work motivation and job satisfaction, these two things are closely related and can lead to employees are more productive so that it will have an impact on better performance. This study aims to re-examine the effect of work motivation and job satisfaction variables on employee performance. This research was conducted on employees of the Denpasar City Social Service located at Jalan Mulawarman No. 2 Dauh Puri Kaja, North Denpasar District, Denpasar City, Bali. The population in this study were all employees of the Denpasar City Social Service with a total of 106 people. The number of samples is 106 people with the saturated sample method. Methods of data collection by observation, interviews and questionnaires. Data analysis techniques used multiple linear regression analysis, multiple correlation, determination, t and F test using SPSS version 25.0 for Windows. Based on the test results, it can be concluded that work motivation has a positive and partially significant effect on employee performance which can be seen from the tvalue of 7.729 and the significant value of the t-test of 0.000 <0.05 so that Ho is rejected and H1 is accepted. That job satisfaction has a positive effect on employee performance which can be seen from the tvalue of 2.498 and the significant value of the t-test of 0.014 <0.05 so that Ho is rejected and H2 is accepted. That work motivation and job satisfaction have a positive and significant effect simultaneously on employee performance which can be seen from the Fcount value of 57.094 with a significance value of Pvalue 0.000 <0.05 so Ho is rejected and H3 is accepted.